Material Encounters and Indigenous Transformations in the Early Colonial Americas Archaeological Case Studies - Hofman, Corinne L.; Keehnen, Floris W.M (The Early Americas: History and Culture, 2019)
Material Encounters and Indigenous Transformations in the Early Colonial Americas brings together 15 archaeological case studies that offer new perspectives on colonial period interactions in the Caribbean and surrounding areas through a specific focus on material culture and indigenous agency. Readership: Scholars in archaeology and early history, graduate students, educated public with an interest in early colonial history of the Americas.